Magnetic metal organic framework material for fluorine ion detection and adsorption as well as preparation method and application of magnetic metal organic framework material
Through the preparation of curcumin-in-situ grafted MOF magnetic materials, the problems of complex preparation, limited adsorption capacity and insufficient selectivity of existing magnetic metal organic frame materials in fluoride adsorption are solved, and efficient adsorption and detection of fluoride ions are achieved. Function, suitable for wastewater treatment and environmental restoration.
Patent Information
- Application Number
- CN202411702782.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
AI Technical Summary
The existing magnetic metal organic frame materials have problems such as complex preparation process, limited adsorption capacity, poor regeneration performance and insufficient selectivity in fluoride adsorption. Some materials use expensive or toxic chemical reagents, which increases production costs and environmental risks.
The preparation method of curcumin in situ grafting MOF magnetic material is adopted. By mixing Fe3O4 nanoparticles with polyvinylpyrrolidone, 3,5-dicarboxyphenylboric acid and cerium nitrate hexahydrate in DMF, curcumin solution and water are added. After stirring, precipitation, washing and drying, the magnetic metal organic frame material Fe3O4@MOF-Cur is obtained to achieve adsorption and detection of fluoride ions.
The material effectively adsorbs fluoride ions in a wide pH range, with an adsorption capacity of up to 99.92 mg/g. It has excellent stability and selectivity, can quickly separate and maintain long-term fluorescence stability, and is suitable for wastewater treatment and environmental restoration.
Smart Images

Figure CN119285985A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of detection and adsorption, and in particular relates to a magnetic metal organic framework material for fluoride ion detection and adsorption, and a preparation method and application thereof. Background Art
[0002] Magnetic Metal-Organic Frameworks (MOF) composites have been widely used in adsorption, separation and catalysis due to their high specific surface area, adjustable pore structure and chemical diversity, especially in the adsorption and detection of fluorides.
[0003] Magnetic MOF composites are usually prepared by two main methods: one is direct synthesis, in which magnetic particles and MOF structures are formed together during the synthesis process. For example, MOF containing ferrite (such as Fe3O4) or other magnetic components is synthesized by solvothermal method. These materials can give full play to their magnetic separation advantages when adsorbing fluorides; the other is post-treatment method, that is, after synthesizing MOF, magnetic materials (such as Fe3O4, CoFe2O4, etc.) are added to it for compounding. This method makes MOF materials magnetic through later chemical modification. Commonly used methods include sol-gel method, coprecipitation method, etc. Existing studies have shown that MOF materials can efficiently adsorb fluorides, and due to the adjustability of their structure, the adsorption performance of fluorides can be further enhanced by changing the structure of metal centers or organic ligands. For example, the Fe3O4@MIL-101(Fe) material achieves efficient adsorption of fluoride in water by embedding Fe3O4 magnetic particles into the MIL-101(Fe)MOF structure; and the Cu-MOFs / Fe3O4 material, which is a composite of copper-based MOF and iron oxide, also shows good fluoride adsorption performance and regeneration ability. The functions of magnetic MOF composite materials in fluoride adsorption are mainly reflected in efficient adsorption of fluoride, magnetic recovery and environmental friendliness. By adjusting the pore structure and surface functional groups of MOF, it can be made to efficiently adsorb fluoride ions in water; in addition, since the magnetic MOF itself has magnetism, the adsorbed fluoride can be recovered through an external magnetic field, avoiding the treatment problems of traditional adsorption materials; compared with traditional adsorption materials (such as activated carbon, ion exchange resin, etc.), MOF materials show higher selectivity and adsorption capacity in fluoride removal.
[0004] Although many studies have explored the use of magnetic MOF materials for fluoride adsorption, there are still some shortcomings. First, the preparation process is complicated. Existing magnetic MOF materials usually require more complicated steps in the synthesis process, especially the introduction of magnetic components, which may require multiple synthesis steps, cumbersome operations, and high requirements for equipment and reagents, which increases the cost and time consumption of large-scale production; second, the adsorption capacity is limited. Although many magnetic MOF composites show high fluoride adsorption capacity, in some cases, the adsorption capacity may not meet expectations, and the regeneration performance of some materials is poor. The adsorption capacity will gradually decrease as the adsorption process proceeds, reducing its practical application effect; third, some magnetic MOF materials are insufficient in the selective adsorption of fluoride, and may adsorb other ions in water at the same time, thereby affecting the efficiency of fluoride removal; finally, some magnetic MOF materials use more complex or expensive chemical reagents in the preparation process, which reduces the environmental protection and cost-effectiveness of the materials. The synthesis of some materials may require the use of toxic chemical reagents or be carried out under high temperature and high pressure conditions, which increases energy consumption and potential environmental risks. Summary of the invention
[0005] The invention provides a magnetic metal organic framework material for fluoride ion detection and adsorption. The material is a curcumin in-situ grafted MOF magnetic material.
[0006] The method for preparing the magnetic metal organic framework material comprises the following steps:
[0007] Disperse Fe3O4 nanoparticles and polyvinyl pyrrolidone in DMF and stir; then add 3,5-dicarboxyphenylboric acid and cerium nitrate hexahydrate and mix evenly; then add curcumin solution and mix evenly; then add water and triethylamine and stir to react; centrifuge, collect precipitates, soak, wash, and dry to obtain a magnetic metal organic framework material.
[0008] In the above preparation method, each component is selected from the following parts:
[0009] 180-250 parts of Fe3O4 nanoparticles, 2.8-3.2 parts of polyvinylpyrrolidone, 80-100 parts of DMF, 250-270 parts of 3,5-dicarboxyphenylboric acid, 260-270 parts of cerium nitrate hexahydrate, 4-6 parts of curcumin solution, 5-6 parts of water, and 1.4-1.8 parts of triethylamine;
[0010] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0011] In a specific embodiment, the mass fractions of the components are as follows:
[0012] 200 parts of Fe3O4 nanoparticles, 3 parts of polyvinylpyrrolidone, 100 parts of DMF, 261 parts of 3,5-dicarboxyphenylboric acid, 270 parts of cerium nitrate hexahydrate, 5 parts of curcumin solution, 5 parts of water, and 1.6 parts of triethylamine;
[0013] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0014] In the above preparation method, the curcumin solution is an ethanol solution of curcumin, and the concentration of the solution is selected from 0.3 to 0.5 mg / mL; preferably 0.4 mg / mL.
[0015] In the above preparation method, the stirring or stirring reaction time is selected from 10 to 18 hours, preferably 12 hours.
[0016] In the above preparation method, the soaking refers to soaking in acetone; the soaking time is selected from 5 to 8 hours, preferably 6 hours.
[0017] In the above preparation method, the Fe3O4 nanoparticles are prepared by the following method:
[0018] Ferric chloride hexahydrate and ferrous chloride tetrahydrate are dissolved in an alcohol-water mixed solution, and then ammonium hydroxide is added and stirred for reaction; after the reaction is completed, the solution is washed and dried to obtain Fe3O4 nanoparticles.
[0019] In the above-mentioned method for preparing Fe3O4 nanoparticles, each component is selected from the following parts:
[0020] 1.3-1.4 parts of ferric chloride hexahydrate, 0.4-0.5 parts of ferrous chloride tetrahydrate, 40-60 parts of alcohol-water mixed solution, 2.5-4 parts of ammonium hydroxide;
[0021] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0022] In a specific embodiment, the mass fractions of the components are as follows:
[0023] 1.329 parts of ferric chloride hexahydrate, 0.489 parts of ferrous chloride tetrahydrate, 50 parts of alcohol-water mixed solution, 3 parts of ammonium hydroxide;
[0024] When the component is a solid component, the portion number represents grams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0025] In the above-mentioned method for preparing Fe3O4 nanoparticles, the alcohol-water mixed solution refers to a mixed solution of ethanol and water, and the volume ratio of the two is 2:3.
[0026] The present invention provides the use of the magnetic metal organic framework material or the magnetic metal organic framework material prepared by the method in adsorbing and / or detecting fluoride ions.
[0027] In the present invention, the magnetic metal organic framework material is mixed with a sample containing fluorine ions to achieve the adsorption of fluorine ions. The detection of fluorine ions can be achieved by the following method:
[0028] The magnetic metal organic framework material is dispersed in water, and then the sample solution is added. After vigorous shaking to ensure sufficient reaction, the fluorescence intensity at 355nm is immediately measured under 260nm excitation; if the emission peak at 355nm increases significantly, that is, the fluorescence intensity increases, it means that the sample contains fluoride ions; if the emission peak at 355nm does not change significantly, that is, the fluorescence intensity remains unchanged, it means that the sample does not contain fluoride ions.
[0029] The beneficial effects of the present invention are:
[0030] The present invention provides a magnetically separable curcumin in-situ grafted MOF core-shell material (Fe3O4@MOF-Cur), which can simultaneously realize the adsorption and detection of fluoride ions. Due to electrostatic adsorption, ligand exchange and fluorine-boron composite action, the material can effectively adsorb fluoride ions in a wide pH range and complex water bodies. The adsorption capacity of the material is as high as 99.92 mg / g or more. The adsorption process conforms to the second-order kinetic model and the Langmuir isothermal adsorption model, and has excellent stability and practicality. In addition, the Fe3O4@MOF-Cur material has a good linear relationship for the fluorescence sensing of fluoride, and its fluorescence maintains good stability for a long time. At the same time, it also has high selectivity for fluoride ions. Since the Fe3O4@MOF-Cur material is separable and has dual functionalization, it provides new ideas and application prospects for the future repair and detection of fluoride ions. Thereby showing good application prospects in the fields of wastewater treatment and environmental remediation, it can also be used for the detection and removal of fluoride ions in krill oil and krill meal. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1TEM images and TEM-EDX element mapping images of the materials; a~c are TEM images of Fe3O4 NPs, d~f are TEM images of Fe3O4@MOF-Cur, and g is TEM-EDX element mapping image of Fe3O4@MOF-Cur;
[0032] Figure 2 FT-IR spectra of Fe3O4, MOF-Cur and Fe3O4@MOF-Cur materials;
[0033] Figure 3 XRD spectra of Fe3O4, MOF-Cur and Fe3O4@MOF-Cur materials;
[0034] Figure 4 is the N2 adsorption-desorption isotherm of Fe3O4@MOF-Cur, and the inset is the pore size distribution of Fe3O4@MOF-Cur;
[0035] Figure 5 The magnetization curves of Fe3O4 and Fe3O4@MOF-Cur;
[0036] Figure 6 The adsorption performance of Fe3O4@MOF-Cur material on fluorine in the test time of 0 to 20 minutes;
[0037] Figure 7 Adsorption kinetics and linear fitting for pseudo-first-order model and pseudo-second-order model;
[0038] Figure 8 The effect of pH on the adsorption of fluorine by Fe3O4@MOF-Cur;
[0039] Fig. 9 Zeta potential of Fe3O4@MOF-Cur at different pH values;
[0040] Fig.10 is the adsorption capacity of Fe3O4@MOF-Cur for fluorine in the presence of different anions;
[0041] Fig.11 is the adsorption isotherm of fluorine on Fe3O4@MOF-Cur, with the initial concentration ranging from 10 to 80 mg / L;
[0042] Fig.12 Langmuir and Freundlich models for fluorine adsorption on Fe3O4@MOF-Cur;
[0043] Fig.13 is the adsorption capacity of Fe3O4@MOF-Cur for fluoride after adsorption-desorption cycles;
[0044] Fig.14 Excitation and emission spectra of Fe3O4@MOF-Cur (a); fluorescence emission spectra of Fe3O4@MOF-Cur after adding different concentrations of fluoride (b);
[0045] Fig.15 is the linear relationship between fluorescence intensity and fluorine concentration;
[0046] Fig.16 The selectivity of Fe3O4@MOF-Cur for fluorine;
[0047] Fig.17 The effect of pH value on the fluorine fluorescence detection performance;
[0048] Fig.18 The fluorescence stability of F3O4@MOF-Cur at different storage times;
[0049] Fig.19 This is the full XPS spectrum of F3O4@MOF-Cur before and after fluorine adsorption;
[0050] Fig. 20 Ce 3d spectra of Fe3O4@MOF-Cur sample before and after fluoride adsorption;
[0051] Fig.21 O1s spectra of Fe3O4@MOF-Cur sample before and after fluoride adsorption;
[0052] Fig. 22 B1s spectra of Fe3O4@MOF-Cur sample before and after fluoride adsorption;
[0053] Fig.23 F1s spectra of Fe3O4@MOF-Cur sample before and after fluoride adsorption;
[0054] Fig.24 UV-visible absorption spectra of MOF, MOF-Cur and Cur (curcumin solution). DETAILED DESCRIPTION
[0055] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0056] Example 1
[0057] The steps for preparing the magnetic metal organic framework material Fe3O4@MOF-Cur are as follows:
[0058] 200 mg Fe3O4 NPs and 3 g polyvinyl pyrrolidone (PVP) were dispersed in 100 mL DMF and stirred for 12 h. 261 mg 3,5-dicarboxyphenylboronic acid and 270 mg cerium nitrate hexahydrate (Ce(NO3)3·6H2O) were added to the above suspension. Then 5 mL of curcumin ethanol solution (0.4 mg / mL) was added. 5 mL of deionized water and 1.6 mL of triethylamine (TEA) were added, and magnetic stirring was performed at room temperature for 12 h. The precipitate was collected by centrifugation, soaked in 50 mL acetone for 6 h, washed with ethanol and water for 3 times, and freeze-dried for 36 h to obtain the magnetic metal organic framework material Fe3O4@MOF-Cur.
[0059] The above Fe3O4 NPs (Fe3O4 nanoparticles) are prepared by the following method:
[0060] 1.329 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.489 g of ferrous chloride tetrahydrate (FeCl2·4H2O) were dissolved in a mixed solution of 30 mL of deionized water and 20 mL of ethanol, and then 3 mL of ammonium hydroxide was added at room temperature and mechanically stirred for 10 min. Then, the mixture was washed alternately with deionized water and ethanol for 3 times and vacuum dried for 12 h to obtain Fe3O4 NPs.
[0061] The TEM images of the above-mentioned Fe3O4 NPs and the TEM images and TEM-EDX elemental mapping images of Fe3O4@MOF-Cur are shown in Figure 2. Figure 1 As shown:
[0062] Fe3O4 nanoparticles are spherical, and there are a lot of pores in the nanospheres, which is conducive to further combining with MOF-Cur ( Figure 1 a~ Figure 1 b). High-resolution transmission electron microscopy shows a clear lattice fringe of about 0.27 nm, corresponding to the Fe3O4(311) crystal plane ( Figure 1 c). Figure 1 d~ Figure 1 f depicts the core-shell structure of the Fe3O4@MOF-Cur sample, where the Fe3O4 nanospheres are tightly wrapped by MOF-Cur nanosheets. Energy dispersive X-ray spectroscopy analysis of the Fe3O4@MOF-Cur nanocomposite Figure 1 g. The elemental composition distribution (B, C, Ce, O, Fe) shows that Fe3O4 and MOF-Cur are uniformly distributed in the Fe3O4@MOF-Cur nanocomposite. These findings further confirm the successful combination of Fe3O4 and MOF-Cur.
[0063] like Figure 2 As shown, FT-IR spectrum analysis demonstrates the successful coordination of organic acid ligands with metal ions in the Fe3O4@MOF-Cur sample, as well as the effect of the introduction of curcumin on the sample structure.
[0064] like Figure 3 As shown in Figure 2, the characteristic peaks of Fe3O4 and MOF-Cur both appear in the XRD diffraction analysis of Fe3O4@MOF-Cur. No impurity peaks were observed, confirming the successful synthesis of Fe3O4@MOF-Cur nanocomposites rather than physical mixtures.
[0065] like Figure 4 As shown in Figure 2, there are micropores and mesopores in the Fe3O4@MOF-Cur structure. The distribution of nested pores further confirms this result. The specific surface area of Fe3O4@MOF-Cur was determined to be 52.8 m 2 / g. The high specific surface area and pore structure can provide a large number of active sites, which is beneficial to the adsorption of fluorine.
[0066] like Figure 5 As shown in Figure 3, although the magnetization intensity of the Fe3O4@MOF-Cur sample is slightly lower than that of the Fe3O4 sample, it still exhibits excellent superparamagnetism. The Fe3O4@MOF-Cur sample can be quickly separated by applying an external magnetic field.
[0067] 1. Fluoride ion adsorption test
[0068] In a typical adsorption experiment, 5 mg of Fe3O4@MOF-Cur sample was dispersed in 40 mL of sodium fluoride solution (20 mg / L). The mixture was placed in a vibrating screen and vibrated at 110 rpm for 30 min. The Fe3O4@MOF-Cur sample was separated by a magnet. Subsequently, the fluoride ion concentration in the supernatant was measured using a fluoride ion selective electrode (PF-2-01). The fluoride ion adsorption capacity (q e ) is calculated by the following formula:
[0069] q e =(C0-C t )V / m
[0070] Where C0 (mg / L) is the initial fluoride ion concentration, C t (mg / L) is the fluoride ion concentration at different vibration times, V(L) is the solution volume, and m(g) is the mass of the Fe3O4@MOF-Cur sample.
[0071] The test results are as follows Figure 6 and Figure 7 As shown:
[0072] Figure 6 The results show that the Fe3O4@MOF-Cur sample has a fast and efficient fluoride ion adsorption capacity. As the available adsorption sites decrease, the adsorption capacity gradually increases within 2 to 14 minutes and reaches saturation at around 14 minutes. The maximum fluoride adsorption capacity of the Fe3O4@MOF-Cur sample is 99.92 mg / g. When the time is further increased to 20 minutes, the adsorption amount remains unchanged, so 14 minutes is considered to be the equilibrium time for fluoride adsorption.
[0073] Figure 7 The correlation coefficient (R 2 =0.99609) was significantly higher than the correlation coefficient of the pseudo-first-order kinetic model (R 2 =0.92038), indicating that the adsorption process of fluoride ions is mainly controlled by chemical adsorption.
[0074] 2. Effects of pH and coexisting ions on adsorption performance
[0075] This study investigated the pH value and coexisting ions (PO4 3- ,I - ,Ac - , Cl - Br - 、SO4 2- 、SIO3 2- ) on the fluoride ion adsorption performance (initial fluoride ion concentration is 20 mg / L). Adsorbent dosage, 5 mg; volume: 40 mL; fluoride concentration, 20 mg / L; coexisting anion concentration, 100 mg / L.
[0076] The test results are as follows Figure 8 , Fig. 9 and Fig.10 As shown:
[0077] Depend on Figure 8 It can be seen that Fe3O4@MOF-Cur has a fast and efficient fluoride ion adsorption ability in a weakly acidic to neutral environment.
[0078] Depend on Fig. 9 It can be seen that as the pH increases, the surface of Fe3O4@MOF-Cur changes from positive charge to negative charge. Since fluoride is negatively charged, there will be electrostatic repulsion between it and the negatively charged adsorbent, which will reduce the adsorption capacity of the adsorbent. However, the adsorption capacity of Fe3O4@MOF-Cur is still very high. This phenomenon shows that electrostatic adsorption is not its main adsorption effect, but also involves ligand reaction.
[0079] Depend on Fig.10 It can be seen that the interfering anions have little effect on the fluorine adsorption process, and Fe3O4@MOF-Cur has stable and efficient fluorine removal performance.
[0080] 3. Adsorption-desorption experiment
[0081] This experiment investigated the recyclability of the Fe3O4@MOF-Cur sample through adsorption-desorption experiments. The initial concentration range was 10-80mg / L. The amount of adsorbent was 5mg; the volume was 40mL. After the adsorption experiment, 0.1M NaOH was added as the eluent for desorption. The desorbed adsorbent was recovered by a magnet and reused in the next fluoride ion adsorption experiment. The cycle was repeated 5 times to test the stability of the adsorption material.
[0082] The test results are as follows Fig.11 , Fig.12 and Fig.13 As shown:
[0083] The adsorption isotherm was plotted using the variation trend of the adsorption amount with the initial fluorine concentration. Fig.11 It can be seen that the adsorption capacity of the Fe3O4@MOF-Cur sample gradually increases with the increase of the initial fluoride concentration and gradually reaches equilibrium at a higher concentration, indicating that the initial fluoride ion concentration gradient is the main driving force for mass transfer between the fluoride solution and Fe3O4@MOF-Cur.
[0084] Depend on Fig.12 It can be seen that the adsorption of fluoride ions by Fe3O4@MOF-Cur sample conforms to the Langmuir monolayer adsorption model, and the adsorption process is mainly chemical adsorption.
[0085] Depend on Fig.13 It can be seen that after 5 consecutive adsorption-desorption cycles, the adsorption amount remained at a high level (79.52 mg / g). The slight decrease in the adsorption amount may be due to the incomplete desorption of some adsorption sites on the surface of Fe3O4@MOF-Cur. It can be seen that the Fe3O4@MOF-Cur nanocomposite has good fluorine adsorption capacity and reusability, and can be further applied to wastewater treatment and environmental remediation.
[0086] 4. Fluoride ion detection test
[0087] In the fluorescence detection experiment, 5 mg of Fe3O4@MOF-Cur sample was dispersed in 40 mL of deionized water. Then, 0.2 mL of sodium fluoride solution of different concentrations (0-100 μM) was added to 1.8 mL of the above mixture. After vigorous shaking to ensure sufficient reaction, the fluorescence intensity at 355 nm was immediately measured under 260 nm excitation.
[0088] The test results are as follows Fig.14 and Fig.15 As shown:
[0089] Depend on Fig.14 It can be seen from a that the Fe3O4@MOF-Cur sample has a maximum emission peak at 355nm under the excitation of 260nm. Fig.14 b It can be seen that with the increase of fluoride ion concentration, the emission intensity of Fe3O4@MOF-Cur at 355nm gradually increases.
[0090] Depend on Fig.15 It can be seen that the Fe3O4@MOF-Cur sample has a good linear relationship for the detection of fluoride ions (R 2 =0.998).
[0091] In summary, Fe3O4@MOF-Cur nanocomposite materials can better realize the detection of fluoride ions and can be used as a fluorescent probe for detecting fluoride.
[0092] 5. Effect of coexisting ions on detection performance
[0093] Considering the complexity of actual detection applications, this experiment studied other ions (PO4 3- ,Ac - , Cl - Br - 、NO 3- 、CO3 2- , Ca 2+ , Cu 2+ ; both are 100μM concentration) interference on the detection performance. In the fluorescence detection experiment, 5mg Fe3O4@MOF-Cur sample was dispersed in 40mL deionized water. Then, 0.2mL of the above interfering ion aqueous solution was added to 1.8mL of the above mixture. After vigorous shaking to ensure sufficient reaction, the fluorescence intensity at 355nm was immediately measured under 260nm excitation. I / I0 represents the ratio of the fluorescence intensity at 355nm after adding the interfering substance to the fluorescence intensity at 355nm without adding the interfering substance.
[0094] The test results are as follows Fig.16 As shown:
[0095] Fe3O4@MOF-Cur has high selectivity for fluoride ions, and other common ions have little effect on its signal changes.
[0096] 6. Effect of pH on Detection Performance
[0097] This experiment explored the effect of pH value on the detection performance of Fe3O4@MOF-Cur material.
[0098] Fe3O4@MOF-Cur suspensions with different pH values (1, 3, 5, 7, 9, 11) were prepared using NaOH and HCl. After adding 0.2 mL of sodium fluoride solution (1 mM), fluorescence measurements were performed under excitation at 260 nm. I / I0 represents the ratio of the fluorescence intensity at 355 nm of the Fe3O4@MOF-Cur suspension after pH adjustment with the addition of 0.2 mL of sodium fluoride solution (1 mM) to the fluorescence intensity at 355 nm of the Fe3O4@MOF-Cur suspension without any adjustment.
[0099] The test results are as follows Fig.17 and Fig.18 As shown:
[0100] Depend on Fig.17 It can be seen that when pH = 7, the sensing performance is optimal; too high or too low pH values will lead to a decrease in material performance.
[0101] Depend on Fig.18 It can be seen that the material exhibits good long-term fluorescence stability within 30 days.
[0102] 7. Adsorption mechanism of fluoride ions by materials
[0103] In order to understand the adsorption process, XPS was used to analyze the changes of Fe3O4@MOF-Cur samples before and after fluoride treatment.
[0104] like Fig.19 As shown, after fluoride treatment, a new F1s peak appeared in the XPS full spectrum, proving that fluoride was successfully captured.
[0105] Fig. 20 The Ce 3d spectra of Fe3O4@MOF-Cur samples before and after fluoride adsorption are shown. Two Ce3d core electron peaks can be observed, corresponding to the spin-orbit splitting of 3d 3 / 2 (904.1eV) and 3d 5 / 2 (885.5eV). These spin-orbit split peaks are further deconvoluted to obtain four peaks, which are labeled as v (881.3eV), v' (885.5eV), u (900.0eV) and u' (904.1eV). After fluoride adsorption, the peak areas in the v and u regions increase significantly, which may be due to the ion exchange between fluoride and Ce-OH to form Ce-F.
[0106] Fig.21 It shows that the O1s spectrum is deconvoluted into three peaks, corresponding to Ce-O, -OH and adsorbed oxygen (OH - / H2O). When the adsorption process reaches equilibrium, a large amount of fluoride exchanges with the OH groups at the Ce defect sites, resulting in the adsorption of oxygen (OH -The relative area of -OH was reduced from 31.5% to 17.0% by fluoride. Meanwhile, fluoride replaced the hydroxyl groups in organic acid ligands and curcumin, causing the relative area of -OH to decrease from 61.3% to 44.6%.
[0107] Fig. 22 The B1s XPS spectrum in the graph shows only one peak, corresponding to B-OH. After fluoride adsorption, the binding energy position shifts toward low binding energy, which can be attributed to the formation of tetrahedral fluoride adducts (RBF) between fluoride and boron groups. 3- ).
[0108] Fig.23 In the F1s XPS spectrum, no fluorine signal was observed before adsorption. After adsorption, the F 1s spectrum can be deconvoluted into two peaks, corresponding to Ce-F and BF, which is consistent with the results of Ce 3d and B1s spectra.
[0109] The trivalent organic boronic acid group has a vacancy z The orbital can accept electrons to cause charge transfer within the molecule and can therefore be used as a fluorescent probe based on PET. Fluorine, which has a high electronegativity, interacts strongly with the boron group, causing the boron atom to shift from sp 2 Hybridization to sp 3 Hybridization. This process inhibits PET, thereby enhancing fluorescence.
[0110] To verify the mechanism of action of PET, the spectral overlap was studied using UV-visible absorption spectroscopy. Fig.24 As shown in the figure, in the range of 200-450nm, the absorption spectra of MOF and Cur basically overlap. This is due to the π-π* electronic transition in the aromatic core, indicating that Cur can obtain part of the excited state energy from MOF. In addition, the absorption spectrum of MOF-Cur shows an extended absorption tail in the range of 500-710nm, which is attributed to the n-π * This indicates the existence of a distinct low-energy mid-gap state in the structure, which induces charge transitions within the molecule.
[0111] also, Fig. 22 and Fig.23 The B1s and F1s spectra in the graph confirm that fluorine adsorption leads to the formation of BF bonds with the boron group and further generates tetrahedral fluorine adducts (RBF 3- ). Therefore, the above results suggest that the inhibition of the PET process is the main mechanism of fluorescence detection.
[0112] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A magnetic metal organic framework material for fluoride ion detection and adsorption, characterized in that: The material is a curcumin in-situ grafted MOF magnetic material.
2. A method for preparing the magnetic metal organic framework material according to claim 1, characterized in that: The steps include: Disperse Fe3O4 nanoparticles and polyvinyl pyrrolidone in DMF and stir; then add 3,5-dicarboxyphenylboric acid and cerium nitrate hexahydrate and mix evenly; then add curcumin solution and mix evenly; then add water and triethylamine and stir to react; centrifuge, collect precipitates, soak, wash, and dry to obtain a magnetic metal organic framework material.
3. The preparation method according to claim 2, characterized in that: The ingredients are selected from the following quantities: 180-250 parts of Fe3O4 nanoparticles, 2.8-3.2 parts of polyvinylpyrrolidone, 80-100 parts of DMF, 250-270 parts of 3,5-dicarboxyphenylboric acid, 260-270 parts of cerium nitrate hexahydrate, 4-6 parts of curcumin solution, 5-6 parts of water, and 1.4-1.8 parts of triethylamine.
4. The preparation method according to claim 2, characterized in that: The curcumin solution is an ethanol solution of curcumin, and the concentration of the solution is selected from 0.3 to 0.5 mg / mL.
5. The preparation method according to claim 2, characterized in that: The stirring or agitation reaction time is selected from 10 to 18 hours; the soaking refers to soaking in acetone; and the soaking time is selected from 5 to 8 hours.
6. The preparation method according to claim 2, characterized in that: The Fe3O4 nanoparticles are prepared by the following method: Ferric chloride hexahydrate and ferrous chloride tetrahydrate are dissolved in an alcohol-water mixed solution, and then ammonium hydroxide is added and stirred for reaction; after the reaction is completed, the solution is washed and dried to obtain Fe3O4 nanoparticles.
7. The preparation method according to claim 6, characterized in that: In the method for preparing the Fe3O4 nanoparticles, each component is selected from the following parts: 1.3-1.4 parts of ferric chloride hexahydrate, 0.4-0.5 parts of ferrous chloride tetrahydrate, 40-60 parts of alcohol-water mixed solution, and 2.5-4 parts of ammonium hydroxide.
8. The preparation method according to claim 6, characterized in that: The alcohol-water mixed solution refers to a mixed solution of ethanol and water, and the volume ratio of the two is 2:
3.
9. Use of the magnetic metal organic framework material according to claim 1 or the magnetic metal organic framework material prepared by the method according to any one of claims 2 to 8 in the adsorption and / or detection of fluoride ions.
10. The use according to claim 9, characterized in that: In the case of fluoride ion detection, the following steps are included: the magnetic metal organic framework material is dispersed in water, and then the sample solution is added, and after vigorous shaking to ensure sufficient reaction, the fluorescence intensity at 355 nm is immediately measured under 260 nm excitation; If the emission peak at 355nm increases significantly, that is, the fluorescence intensity increases, it means that the sample contains fluoride ions; if the emission peak at 355nm does not change significantly, that is, the fluorescence intensity remains unchanged, it means that the sample does not contain fluoride ions.